ANALISIS SEWA MENYEWA TANAH DENGAN SISTEM BAYAR MUSIM PANEN MENURUT FATWA DSN NO. 112/DSN-MUI/IX/2017 (STUDI KASUS DI DESA LENGKESE KABUPATEN TAKALAR) - Muh. Aqsyar; Agung Daeng Rizky, Hatika Wulandari Lewa, Wawan Anggara (JOURNAL OF LAW AND NATION, 2025)
The purpose of this study is to determine the lease of land with a harvest season pay system based on DSN Fatwa No. 112/DSN-MUI/IX/2017. This research is field research (Field Research) data sources in this study are primary, secondary and tertiary data sources. Data collection techniques using observation, interviews, and documentation. In analyzing the data this research uses descriptive analysis. Leasing land with a harvest season payment system in Lengkese Village, Takalar Regency is carried out by landowners and tenants who are able to manage and without coercion. The implementation of ijab qabul between the landowner and the tenant is carried out orally without any written evidence. Payment of rent at the time of the lease contract is made when the first harvest season arrives. However, in practice, even though it has been given leeway for payment until the first harvest season arrives, there are still tenants who do not fulfill their obligations on the grounds of experiencing losses and various other reasons. The land tenant deliberately delays the time of payment of rent even though it has been harvested. The parties in this case the land tenant and the landlord are asked to deliberate for consensus, but if there is no consensus in deliberation then the step taken is to settle at the dispute resolution institution. Based on this, it can be concluded that land leasing with a harvest season payment system in Lengkese Village, Takalar Regency is not fully in accordance with the provisions in DSN MUI No. 112/DSN-MUI/IX/2017.